The Influence of the Jigsaw Learning Model on Self-Esteem and Basic Basketball Technical Skills in Elementary Schools - Andika Nur Fajri; Wildan Alfia Nugroho; Agus Mahendra (Universitas Negeri Semarang, 2026)
The Jigsaw Learning Model is a learning strategy that emphasizes cooperation among students by dividing the material into small sections that are studied in groups. Each group member is responsible for studying one section of the material, then meets with members of other groups who are studying the same section (called expert groups), and then returns to their original group to teach the material they have understood. The purpose of this study is to analyze improvements in basic basketball skills and self-esteem through the application of the Jigsaw cooperative learning model. The research method used is Classroom Action Research (CAR) with a pre-experimental approach. The research subjects are students in class VC, who were divided into small, heterogeneous groups. The research data was analyzed using Excel 2021. The results showed an improvement in the basic basketball skills of students in Class VC at Elementary School 178 Gegerkalong KPAD following the implementation of the jigsaw learning model. The students’ average score increased from 41 in the pre-cycle phase to 62.4 at the end of Cycle II. Additionally, students’ self-esteem levels also increased, from an initial average score of 60.45 to 78.62 following the implementation of the instructional interventions. In conclusion, the implementation of the jigsaw learning model, carried out over four interventions across two cycles, proved effective in enhancing both the basic basketball skills and self-esteem of students in Class VC at Elementary School 178 Gegerkalong KPAD. The results of the students’ basic basketball skill tests showed a significant improvement from the pre-cycle results to the fourth intervention in Cycle II. Implicitly, the Jigsaw cooperative learning model can be used as an effective learning strategy to improve students’ basic basketball skills.